The influence of job burnout on the attention ability of army soldiers and officers: Evidence from ERP - Wu, Lin; Chen, Yanfeng; Liu, Xufeng; Fang, Peng; Feng, Tingwei; Sun, Kewei; Ren, Lei; Liang, Wei; Lu, Huijie; Lin, Xinxin; Li, Yijun; Wang, Lingling; et al. (Frontiers in Neuroscience, 2022)
Burnout is one of the most widespread mental problems in society today and seriously affects the mental health and combat effectiveness of soldiers and officers. Herein, the effect of burnout on individual attention is studied from the perspective of neuroelectrophysiology. 1155 army soldiers and officers were included in this investigation and completed the Soldiers' Job Burnout Scale. A total of 42 soldiers and officers were randomly selected from those with burnout and without burnout, respectively, to participate in an event-related potential (ERP) study using an oddball task. The characteristics of P300 at Fz, FCz, Cz, CPz and Pz were recorded and analyzed by repeated-measures analysis of variance (ANOVA). P<0.05 was the criterion for a significant difference. The total average score for the soldiers and officers was 0.74±0.46, and the rate of detection was 29.85%. For P3a, the amplitude of Fz, FCz, Cz, CPz and Pz in the burnout group were significantly lower than those in the control group, and the main effect between groups was significant. The average amplitude of P3a evoked in the central parietal area was larger than that in the prefrontal area, and the main effect of the electrode was significant. The interaction effect between electrode and group was significant. For P3b, the amplitudes of the five electrodes in the burnout group were significantly lower than those in the control group, and the main effect between groups was significant. The average amplitude of P3b evoked in the parietal region was larger than those in the prefrontal and central parietal regions, and the main effect of the electrode was significant. The interaction effect between electrode and group was significant. There is a certain degree of job burnout in army soldiers and officers. The voluntary and involuntary attention of individuals with burnout are both affected to some extent, as reflected in the decrease in P3a and P3b amplitude. The results suggest that P3a and P3b can be used as indicators to monitor cognitive neural function in soldiers and officers with burnout and can also be used as a reference for evaluating the effect of cognitive training and screening methods.